2004
DOI: 10.5194/acp-4-627-2004
|View full text |Cite
|
Sign up to set email alerts
|

A time-resolved model of the mesospheric Na layer: constraints on the meteor input function

Abstract: Abstract.A time-resolved model of the Na layer in the mesosphere/lower thermosphere region is described, where the continuity equations for the major sodium species Na, Na + and NaHCO 3 are solved explicity, and the other shortlived species are treated in steady-state. It is shown that the diurnal variation of the Na layer can only be modelled satisfactorily if sodium species are permanently removed below about 85 km, both through the dimerization of NaHCO 3 and the uptake of sodium species on meteoric smoke p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
238
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 164 publications
(267 citation statements)
references
References 43 publications
10
238
0
Order By: Relevance
“…In the mesosphere and lower thermosphere (MLT), Na + ions and sodium bicarbonate (NaHCO 3 ) are the major reservoir species above and below the atomic Na layer, respectively (Plane et al, 1999;Plane, 2004). Due to the long residence time (∼7 days) of ablated sodium in the region between 80 and 100 km (Plane, 2004), and the comparatively short lifetimes of the ratedetermining chemical reactions that convert sodium between atomic Na and these reservoirs, the chemistry reaches a photochemical steady-state on the timescale of vertical transport by eddy or molecular diffusion . Consequently, atmospheric chemistry plays a key role in determining the atomic Na distribution.…”
Section: Global Latitudinal and Seasonal Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mesosphere and lower thermosphere (MLT), Na + ions and sodium bicarbonate (NaHCO 3 ) are the major reservoir species above and below the atomic Na layer, respectively (Plane et al, 1999;Plane, 2004). Due to the long residence time (∼7 days) of ablated sodium in the region between 80 and 100 km (Plane, 2004), and the comparatively short lifetimes of the ratedetermining chemical reactions that convert sodium between atomic Na and these reservoirs, the chemistry reaches a photochemical steady-state on the timescale of vertical transport by eddy or molecular diffusion . Consequently, atmospheric chemistry plays a key role in determining the atomic Na distribution.…”
Section: Global Latitudinal and Seasonal Variationsmentioning
confidence: 99%
“…Consequently, atmospheric chemistry plays a key role in determining the atomic Na distribution. Na is converted to NaHCO 3 via the following sequence of reactions (Plane, 2004):…”
Section: Global Latitudinal and Seasonal Variationsmentioning
confidence: 99%
“…Below 90 km, the main chemical reaction that produces sodium atoms is NaHCO 3 + hv → Na + HCO 3 . The reaction rate coefficients are listed in Table 1 of Plane [2004]. The potential correlations between SSLs and the temperature structure have also been studied previously [Hansen and von Zahn, 1990;Zhou et al, 1993;Gardner et al, 1995;Delgado et al, 2012].…”
Section: Temperature Mechanismmentioning
confidence: 99%
“…And a less pronounced link, or absence of a link, between Es and SSL is observed below 95 km [Hansen and Von Zahn, 1990]. Second, the complex SSL chemical process has been published [Cox and Plane, 1998;Collins et al, 2002;Plane, 2003Plane, , 2004 while SSLs and temperature have been observed simultaneously [Hansen and Von Zahn, 1990;Gardner et al, 1993Gardner et al, , 1995Batista et al, 2002]. Temperature-independent conjecture Zhou and Mathews, 1995] and modeling [Delgado et al, 2012] along with sporadic neutral metal atom layers have been studied and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently attracted a renewed interest, because, besides the scientific questions related to the origin and the vertical distribution of the layer, the mesospheric sodium is of major importance in astronomy, where it is used to produce an artificial star on which to base guidance for adaptive optics with a lidar illumination. Although extensive data exist about the mesospheric sodium layer measured from particular sites, very little is known about the geographical distribution (Plane, 2004). GOMOS has demonstrated a new method of studying the sodium layer, and has provided the first global mesospheric sodium climatology made so far .…”
Section: Detection and Climatology Of The Natural Sodium Layermentioning
confidence: 99%